2022
DOI: 10.1038/s43587-022-00177-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-GWAS functional analysis identifies CUX1 as a regulator of p16INK4a and cellular senescence

Abstract: Accumulation of senescent cells with age is an important driver of aging and age-related diseases. However, the mechanisms and signaling pathways that regulate senescence remain elusive. In this report, we performed post-genome-wide association studies (GWAS) functional studies on the CDKN2A/B locus, a locus known to be associated with multiple age-related diseases and overall human lifespan. We demonstrate that transcription factor CUX1 (Cut-Like Homeobox 1) specifically binds to an atherosclerosis-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 62 publications
5
22
0
Order By: Relevance
“…To explain such a dose-sensitivity of CUX1 on expression of its target genes, an analog model has been proposed: long-distance low-affinity CUX1 binding sites loop to the gene promoters, incorporating input from other genomic features to fine-tune the transcriptional response 7 . This same fine-tuning mechanism may apply to this fSNP, consistent with this notion, Jiang et al show that CUX1 has a higher affinity to the risk allele than to the non-risk allele 5 . Indeed, in the context of arterial ECs, this fSNP coincides with active enhancer marks, likely co-regulating CDKN2A and other genes (p14ARF and CDKN2B) and CDKN2B-AS1 (ANRIL) within the CDKN2A/B locus through a long-range interaction.…”
Section: Mainsupporting
confidence: 60%
See 1 more Smart Citation
“…To explain such a dose-sensitivity of CUX1 on expression of its target genes, an analog model has been proposed: long-distance low-affinity CUX1 binding sites loop to the gene promoters, incorporating input from other genomic features to fine-tune the transcriptional response 7 . This same fine-tuning mechanism may apply to this fSNP, consistent with this notion, Jiang et al show that CUX1 has a higher affinity to the risk allele than to the non-risk allele 5 . Indeed, in the context of arterial ECs, this fSNP coincides with active enhancer marks, likely co-regulating CDKN2A and other genes (p14ARF and CDKN2B) and CDKN2B-AS1 (ANRIL) within the CDKN2A/B locus through a long-range interaction.…”
Section: Mainsupporting
confidence: 60%
“…In this issue of Nature Aging, through screening of SNPs in the CDKN2A/B locus, Jiang et al find an additional layer of the mechanism, whereby the transcription factor CUX1 activates CDKN2A expression through direct binding to an 2 atherosclerosis-associated functional SNP (rs1537371), thus promoting senescence in human arterial endothelial cells (ECs) (Fig. 1a) 5 .…”
Section: Mainmentioning
confidence: 99%
“…Previously, we identified that homeodomain transcription factor CUX1, as one of the six proteins in a complex, activates p16 INK4a ‐dependent cellular senescence via its specific binding to the atherosclerosis‐associated fSNP rs1537371 on the CDKN2A/B locus in human arterial ECs (Jiang et al, 2022 ). Another one of these six proteins in the complex is SATB2, also known as a homeodomain transcription factor (Britanova et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we performed a luciferase reporter assay using a reporter construct that contains the risk allele A from the fSNP rs1537371 also in the SATB2 shRNA knockdown cells. This reporter construct was previously used to validate the fSNP rs1537371 by detecting the allele‐imbalanced luciferase activity that shows the risk allele A having more luciferase activity than the nonrisk allele C (Jiang et al, 2022 ). Our data, as shown in Figure 1c (right), indicate that downregulation of SATB2 resulted in a significantly increased luciferase activity ( p ‐value = 0.019) by comparing the SATB2 shRNA knockdown cells with the scrambled shRNA control cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation